1998
DOI: 10.1001/archfami.7.6.583
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate Treatment to Prevent Osteoporotic Fractures

Abstract: Alendronate sodium, an aminobisphosphonate, has been approved by the Food and Drug Administration for the prevention and treatment of osteoporosis in postmenopausal women, thus providing an effective alternative to estrogen replacement therapy in women who cannot or will not take estrogen. Large, randomized, controlled trials have demonstrated approximately a 50% reduction in vertebral, hip, and wrist fractures. Efficacy and safety beyond 3 years has not been determined. To avoid esophagitis and maximize absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…A unique observation that is particularly concerning is that 10% of residents were taking a bisphosphonate but were not taking vitamin D or a multivitamin. Alterations in calcium and phosphorus metabolism can occur with bisphosphonate use, so supplemental calcium and vitamin D are recommended [35].…”
Section: Discussionmentioning
confidence: 99%
“…A unique observation that is particularly concerning is that 10% of residents were taking a bisphosphonate but were not taking vitamin D or a multivitamin. Alterations in calcium and phosphorus metabolism can occur with bisphosphonate use, so supplemental calcium and vitamin D are recommended [35].…”
Section: Discussionmentioning
confidence: 99%
“…To determine gene expression levels, total RNA was extracted from cells at each experimental time point using TRIzol ® reagent (Thermo Fisher Scientific, Inc., Waltham, MA, USA). Total RNA (1 µg) was reverse-transcribed using oligo (dT) 20 primer and SuperScript III First-Strand Synthesis System (Invitrogen; Thermo Fisher Scientific, Inc.) according to the manufacturer's protocol. The relative mRNA level of the target gene was quantified using qPCR with a TaqMan �robe and TaqMan Master Mix in a LightCycler Nano instrument (both Roche Diagnostics GmbH, Mannheim, Germany), according to the �anufacturer's �rotocol.…”
Section: Validation Of Gene Expression and Rt-qpcrmentioning
confidence: 99%
“…Clinically, osteoporotic fractures result in notable mortality and morbidity (18). Alendronate acid, a bisphosphonate, is the primary agent used to prevent and treat osteoporosis (20)(21)(22). Pharmacokinetic studies have indicated that ~50% of the alendronate absorbed into the body binds to bone surface, while the other 50% is rapidly excreted from the kidneys (20,23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O alendronato de sódio é uma droga aprovada pelo FDA (Food and Drug Administration) para prevenção e tratamento da osteoporose em mulheres pós-menopausadas, como alternativa eficaz à terapia de reposição estrogênica, especialmente para aquelas que não podem ou não farão o uso deste hormônio (5) . Recomenda-se que a droga seja tomada pelo menos 30 minutos antes da primeira alimentação ou bebida do dia com um copo cheio de água (180-240 mL), e que se evite deitar ao menos por um período de 30 minutos que sucedem a sua ingestão (2) …”
Section: Discussionunclassified